Herpetofauna and Their Potential Threats in Karimata Island, Indonesia - Pratama, Ferdian Wira; Fauzan, Opi; Luthfi, Muhammad (Journal of Tropical Biodiversity and Biotechnology, 2024)
Karimata Island is an island about 100 km west of Borneo, causes geographical isolation and generally always shows an impact on the diversity of animal communities that are less, one of the communities affected is herpetofauna. Herpetofauna is very important in an ecosystem so it is necessary to conduct a survey. The survey was conducted from April 1 to April 7, 2023 in Betok Jaya Village, Karimata Island which was divided in 3 observation areas based on habitat type using the Visual Encounter Survey method. Herpetofauna found consisted in 22 species divided into 5 species of amphibians and 17 species of reptiles with a total of 43 individuals. Herpetofauna located adjacent to human areas is vulnerable to various disturbances such as maritime transportation activities, household waste pollution and land clearing, which can be a threat to the herpetofauna community of Karimata Island.